Personal assistance services for disabled people in Ireland: "they meet the criteria for supports but we don't have the resources to provide the services" - Eamonn Carroll; Ciarán Mac Domhnaill; Selina MacCoy (The Economic and Social Research Institute (ESRI), 2023)
Personal assistance (PA) services have been an evolving part of Irish provision for people with physical and sensory impairments for roughly three decades, but the lack of national standards for allocation, provision or data collection have made it an opaque system characterised by piecemeal or ad hoc local solutions to increasing need. This study approaches the system through the perspective of institutional insiders, eliciting the views and experiences of state and NGO based institutional stakeholders about the PA system and its challenges. A two-step exploratory mixed-method design, incorporating a series of qualitative interviews and a survey of HSE disability managers, provides rich insights into the nature of PA provision in Ireland. The findings illustrate and explore several chronic issues facing the PA system, most notably around under-funding, inadequate administrative data records and variation in allocation and provision across the country.
Keywords: 330; personal assistance; independent living; Ireland; Health Service Executive; United Nations Convention on the Rights of Persons with Disabilities